RNA Editing and Drug Discovery for Cancer Therapy - Wei-Hsuan Huang; Chao-Neng Tseng; Jen-Yang Tang; Cheng-Hong Yang; Shih-Shin Liang; Hsueh-Wei Chang (The Scientific World Journal)
RNA editing is vital to provide the RNA and protein complexity to regulate the gene expression. Correct RNA editing maintains the cell function and organism development. Imbalance of the RNA editing machinery may lead to diseases and cancers. Recently, RNA editing has been recognized as a target for drug discovery although few studies targeting RNA editing for disease and cancer therapy were reported in the field of natural products. Therefore, RNA editing may be a potential target for therapeutic natural products. In this review, we provide a literature overview of the biological functions of RNA editing on gene expression, diseases, cancers, and drugs. The bioinformatics resources of RNA editing were also summarized.